The Response to the COVID-19 Pandemic in Taiwan - Sitthiwong, Akkapong (Thai Journal of East Asian Studies, 2023)
This research studied 1) development of Novel Coronavirus 2019 (COVID-19) pandemic resolutions in Taiwan 2) Taiwanese challenges and successes in dealing with the pandemic. During the early spread of the COVID-19 pandemic, Taiwan managed to control the public health challenge. Different factors motivated this national achievement. As Taiwan is blocked by China from participation in the World Health Organization (WHO), its government is necessarily self-reliant. Due to Chinese restricted vaccine provision following the One China Principle, Taiwan relied on the United States of America (USA) to donate significant amounts of vaccine, adding to Taiwanese status as regional area of geopolitical rivalry between the USA and China. Data was collected from published articles, media reports, scholarly research, and interviews with foreigners living in Taiwan during the pandemic.